Dos fragmentos recombinantes derivados de la proteína secretada con dominio de repetición de trombospondina alterado (SPATR) de Plasmodium vivax interactúan con reticulocitos, pero no con células hepáticas humanas (2021)
The Plasmodium human invasion cycle involves many proteins enabling it to interact with and invade host cells. Recent studies in species such as Plasmodium falciparum have shown that the secreted protein with altered thrombospondin repeat (SPATR) protein is expressed in sporozoites and merozoites, is antigenic and essential for the invasion of erythroid and liver cells. However, little is known about its host cell binding activity in Plasmodium vivax, one of the most widely-distributed parasites worldwide. This work has thus been focused on determining two PvSPATR recombinant fragments’ human hepatocyte and reticulocyte binding activity. Bl21-AI cells transformed from recombinant plasmids containing two PvSPATR fragments’ encoding sequences were used for expressing rPvSPATR-F1 and rPvSPATR-F2 and then purified by affinity chromatography. rPvSPATR-F1 and rPvSPATRF2 binding to human hepatocytes and reticulocytes was quantified by flow cytometry. Both recombinant regions only interacted with human reticulocytes, suggesting PvSPATR participation in receptor-ligand type interactions during the erythrocyte stage and that these regions could be targets of action for preventing this disease.